Chikungunya fever: pathogenesis and mechanisms underlying pain symptoms - Sun, Wuping; Shi, Shuqi; Liao, Shengyun; Zhai, Mingzhu (Frontiers in Immunology, 2025)
Chikungunya fever (CHIKF), caused by the Chikungunya virus (CHIKV) and transmitted by Aedes mosquitoes, has rapidly evolved from localized outbreaks to a significant global health threat. While the initial high fever is often debilitating, it is the severe and frequently long-lasting pain, affecting joints (arthralgia), muscles (myalgia), and sometimes nerves (neuropathic pain), that truly characterizes the disease’s impact on sufferers. This review explores how CHIKV infection triggers both acute pain and persistent chronic pain. We examine the mechanisms by which the virus directly damages tissues, incites extensive inflammation, invades the nervous system, and potentially manipulates the immune response, leading to autoimmune-like attacks. Understanding these processes is essential, as current treatments mainly focus on symptom management, and there are no specific antiviral therapies available. Identifying the factors that contribute to the persistence of pain is critical for developing targeted and more effective therapeutic interventions, ultimately alleviating the long-term burden of this debilitating disease.